Effects of independent double-gated configuration on polycrystalline-Si nonvolatile memory devices - Chen, Wei-Chen; Lin, Horng-Chih; Chang, Yu-Chia; Huang, Tiao-Yuan (My University, 2009)
A polycrystalline-Si thin-film transistor configured with independent double-gated structure and ultrathin channel film is proposed for use as a Si-oxide-nitride-oxide-Si memory device. Taking advantage of additional control gate bias offered by the independent double-gated scheme in addition to the driving gate, this work demonstrated that the reading window and programming efficiency can be improved by applying a proper control gate bias. It is also found that the relationship between programming/erasing speed and control gate bias is strongly related to channel film thickness. Our results indicate that the independent double-gated device possesses promising potential for future nonvolatile memory applications. (C) 2009 American Institute of Physics. [doi: 10.1063/1.3238362]